Fakka AL Harati: An anthropological study in Khanat Al-Musayyab for Al-Harati chicken - hamzh, Ali Kadhim (Al-Adab Journal, 2022)
The research deals with an anthropological study of a phenomenon worthy of attention, which is Fakka Al Harati, as the stud community calls it. Ln a specific place called the Musayyab box for the Harati chicken, it has a specific time and is played by amateur people who are fond of this game, called the criminal or the people of chickens, and this game has its fans and its lovers. Through this research, we tried to describe the phenomenon in an ethnographical description, using anthropological research techniques that have proven effective in this field.